Mobilization vs. Demobilization Discourses on Social Media. (3rd September 2021) - Kligler-Vilenchik, Neta; de Vries Kedem, Maya; Maier, Daniel; Stoltenberg, Daniela
ABSTRACT: While scholarly attention has been devoted to social media's potential mobilizing function, they may also contribute to demobilization discourses: social communication actively promoting nonvoting. This paper examines discourses around mobilization vs. demobilization in the context of the municipal elections in Jerusalem. As the sweeping majority of East Jerusalem Palestinians have continuously been boycotting Jerusalem's municipal elections, this is a potent case through which to examine how demobilization functions in action, through social media conversations. Using a mixed-methods analysis of Twitter contents as structured by different languages, our findings show how mobilization and demobilization discourses can co-occur during the same election event. Users of different languages – reflecting different social and political identities – interpret the elections in contrasting ways, with tangible implications for (in)equality in political participation. The study thus contributes theoretically to several domains of political communication, including election studies, local politics, and language fragmentation in online political discourse.